Kasih Radikal Lukas Untuk Mengatasi Ekstremisme Agama - Eni Marlina Sihombing; Ncihur Fronika Solin; Harjaya Situmeang; Yersi Berutu (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
religious extremism often arises from a narrow understanding of religious teachings, which leads to hatred and violence. leading to hatred and violence. This article examines how the teaching ofradical love in the Gospel of Luke can be a solution to overcome religious extremism. religious extremism. Radical love in Luke teaches the importance of loving enemies, accepting unconditionally, and promoting peace. This teaching has three main functions: encouraging change in individuals and society, reducing tensions between groups, and replacing hatred with love.As such, Luke's radical love becomes a practical approach to create peace and reduce conflicts brought about by extremism in society.